Women in prison : an insight into captivity and crime - Cherukuri, Suvarna (Foundation Books, 2008)
Women in Prison takes a look at the multiple specificities that bring women into the prison system. Drawing on empirical sources and original research, and relying primarily on interviews of women inmates, this book explores the contexts of female crime and punishment in India and looks at gendered disciplinary mechanisms that are used to control women inmates. The work invokes not only a sense of history in understanding womens crimes and imprisonment, but also engages in a critical dialogue in terms of gender, caste, culture and sexuality. Unique in its analysis of the lives of women prisoners within social and legal contexts, the book is a major contribution to international literature on womens offences and their experience of imprisonment.